Managerial discretion and performance in China : towards resolving the discretion puzzle for Chinese companies and multinationals - Wulferth, Hagen (Contributions to Management Science, 2013)
The theoretical and empirical literature to date has fallen short of reaching a consensus as to whether granting more managerial discretion to managers tends to enhance, not alter or diminish organisational performance (the discretion puzzle). This book aims to build a bridge between these contradictory results by synthesising principal-agent theory, stewardship theory, and managerial discretion theory into a new empirically-validated model. Using a representative sample of 'double-blind' interviews with managers of 467 firms in China and applying partial least squares path modelling (PLS), the study identifies a potential cause of the discretion puzzle: the failure of the extant literature to account for granularity in the way that managers use their discretion. This generates far-reaching implications for theoretical and empirical research as well as practical recommendations for managing managers in multinationals and Chinese companies.